Motion characteristics of Division I college Field Hockey: Female Athletes in Motion (FAiM) Study - Vescovi, J. D.; Frayne, D. H. (International Journal of Sports Physiology and Performance, 2015)
Purpose: To examine locomotor demands and metabolic-power characteristics of National Collegiate Athletic Association (NCAA) field hockey matches. Methods: Using a cross-sectional design, global positioning system (GPS) technology tracked Division I field hockey players from 6 teams during 1 regular-season match (68 player observations). An ANOVA compared locomotor demands and metabolic-power characteristics among positions. Paired t tests compared dependent variables between halves. Results: Defenders played 5-6 min more than midfielders, whereas midfielders played 6-7 min more than forwards. Defenders covered less relative distance (98 m/min) than forwards and midfielders (110-111 m/min), as well as more low-intensity running than forwards and less high-intensity running than midfielders. Lower mean metabolic power (9.3 W/kg) was observed for defenders than forwards and midfielders (10.4 W/kg). There was no difference in playing time between halves; however, all 3 positions had a reduction in relative distance (7-9%) and mean metabolic power (8-9%) during the second half. Conclusions: Despite more playing time, defenders covered less relative distance and had lower mean metabolic power than other positions. Moderate-intensity, high-intensity, and sprint distance were similar between positions, highlighting the greater relative demands on forwards because they tended to have the least amount of playing time. The reduction of key metrics during the second half was similar among positions and warrants further investigation. These initial results can be used to design position-specific drills or create small-sided games that replicate match demands for NCAA athletes, thus helping establish strategies for developing physiological ability of players at this level.